Antimicrobial resistance in veterinary dermatology: Literature review on the impact of antibiotic use in skin infections in small animals (Research, Society and Development, 2025)
Antimicrobial resistance (AMR) represents a critical challenge in veterinary medicine, especially in small animal skin infections such as superficial bacterial folliculitis. Infections caused by Staphylococcus pseudintermedius have become increasingly difficult to treat due to the emergence of methicillin-resistant (MRSP) and multidrug-resistant (MDR) strains. This article aims to reviewco the main factors contributing to AMR, including the indiscriminate use of antibiotics, lack of accurate diagnosis, and the impact of underlying clinical conditions such as atopic dermatitis. Advances in diagnosis stand out, with the use of technologies such as MALDI-TOF and susceptibility tests, which are crucial to guide effective therapies. The review also addresses the most recent recommendations for therapeutic management, prioritizing the rational use of antimicrobials. Antibiotics such as amoxicillin-clavulanate, cephalexin and clindamycin remain first-line treatments for susceptible infections, while alternative options such as rifampin and linezolid are indicated only in cases of proven resistance. Furthermore, preventative strategies, such as improvements in hygiene practices and the use of topical therapies, are highlighted as effective methods to reduce the need for systemic treatments and minimize the selection of resistant strains. Finally, this article emphasizes the relevance of an integrated One Health approach, which recognizes the interconnection between animal, human and environmental health, as an indispensable strategy for tackling AMR.